Case report: Lung transplantation for treatment of paraquat intoxication: timing of transplantation - Li, Congcong; Cai, Hongfei; Meng, Fanyu; Meng, Fanjie; Tang, Ze; Tang, Ying; Chen, Ying; Cui, Youbin; Li, Yang (Frontiers in Pharmacology, 2023)
To analyze the optimal timing of lung transplantation and summarize postoperative complications and their management after paraquat poisoning. Methods: Here, we present the clinical course of a 17-year-old boy with paraquat poisoning, in whom bilateral lung transplantation (LT) was performed. We reviewed the eight previously published articles relevant to LT after paraquat poisoning to summarize the therapeutic strategy. Results: A 17-year-old boy was admitted to the hospital after ingestion of 30-50 mL 25% paraquat. Mechanical ventilation was initiated on the 25 th day after intoxication. Venovenous extracorporeal membrane oxygenation was initiated on the 26 th day. Sequential bilateral LT was performed on the 27 th day. Several complex postoperative complications occurred and the patient was discharged on the 50 th day postoperatively. Eight case reports were included in the literature review, including 11 patients with paraquat poisoning undergoing LT. Three patients died due to paraquat poisoning leading to fibrosis in the transplanted lungs or postoperative complications. Eight patients survived during follow-up. Conclusions: LT after herbicide poisoning should be planned when hepatorenal function starts to recover, and waiting for complete recovery is unnecessary. Prevention of infection before surgery is important to reduce the incidence of postoperative infection. Complex perioperative complications caused by the herbicide itself or the late timing of transplantation can be successfully managed by a multidisciplinary team.